2011
DOI: 10.1103/physrevlett.106.180403
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence and Disorder in Quantum Walks: From Ballistic Spread to Localization

Abstract: We investigate the impact of decoherence and static disorder on the dynamics of quantum particles moving in a periodic lattice. Our experiment relies on the photonic implementation of a one-dimensional quantum walk. The pure quantum evolution is characterized by a ballistic spread of a photon's wave packet along 28 steps. By applying controlled time-dependent operations we simulate three different environmental influences on the system, resulting in a fast ballistic spread, a diffusive classical walk, and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
391
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(410 citation statements)
references
References 31 publications
(31 reference statements)
9
391
0
2
Order By: Relevance
“…Besides theoretical [18,19] and numerical [20] studies, this effect has also been observed experimentally [21].…”
Section: Introductionmentioning
confidence: 62%
“…Besides theoretical [18,19] and numerical [20] studies, this effect has also been observed experimentally [21].…”
Section: Introductionmentioning
confidence: 62%
“…Depending on the types of disorder and symmetries, experiments and theory on DTQWs have already seen both Anderson localization, 39 and delocalization. 40 Our generalized scattering matrix formalism allows a continuation of this research to more general multistep DTQWs.…”
Section: Discussionmentioning
confidence: 99%
“…Such configurations have been systematically employed to investigate a number of issues ranging from discrete quantum walks [44][45][46][47] to Bloch oscillations and fractal patterns [43,48]. While spatial realizations of such mesh lattices have also been reported [47,49], time-multiplexed fiber loop schemes have so far demonstrated a high degree of flexibility [43,45].…”
Section: Optical Mesh Lattices In the Time Domainmentioning
confidence: 99%